Analisis Efektivitas dan Kontribusi Penerimaan Pajak Bumi dan Bangunan Perdesaan dan Perkotaan (PBB-P2) dalam Upaya Peningkatan Penerimaan Pajak Daerah di Kota Bekasi Tahun 2017-2021 - Nisa Andriani; Ratih Kumala (Jurnal Ilmu Administrasi Publik, 2022)
The realization of PBB-P2 and regional tax revenue fluctuates every year. PBB-P2 is one of the contributions to PAD. In addition, Bekasi is known for its property sector, so the sale and purchase transactions of land and buildings will increase, which will affect the increase in PBB-P2 for Bekasi. The purpose of this study is to determine and analyze the effectiveness and contribution of PBB-P2 in increasing local tax revenue in Bekasi, as well as to analyze the inhibiting factors and efforts made in collecting PBB-P2 in Bekasi. This study used the descriptive qualitative method. The data collection was observation, interviews, documentation, and triangulation. The results showed that overall, the effectiveness of PBB- P2 has increased by an average of 96.62% which was very effective. The contribution of PBB-P2 revenue as a whole fluctuated with an average of 18.75%, which was not optimal. The obstacles to the PBB-P2 revenue in Bekasi were in the form of an un-updated database, incomplete addresses of taxpayers or those who have moved, the not evenly distributed socialization on the easy payment system which caused a decrease in public awareness, and the ineffective use of social media regarding payment information. To overcome obstacles, some efforts must be made. The efforts were in the forms of socialization via social media and other electronic media, intensive billing and combing operations, updating data every year, and getting closer to taxpayers.